Islamic media algorithms and halal perception in Malaysia - Jamaludin, Mohammad Aizat; Rosli, Nur Liana Izzaty; Ibrahim, Muhammad Irhammudin (Universiti Teknologi MARA (UiTM), Malaysia, 2025)
In today’s algorithm-driven digital age, Islamic and Halal content is often promoted not for its authenticity or quality, but for its ability to attract engagement, frequently amplified by deceptive artificial intelligence (AI) systems. This article examines how viral trends and algorithms shape public perceptions of the Halal concept online, particularly through sensational, divisive, or misleading Islamic content. The study aims to assess Muslim users’ responses to online Halal-related material and evaluate the influence of algorithmic curation on their perceptions and decisions. Using a qualitative approach such as content analysis, findings reveal that platform algorithms contribute to misinformation, confusion, and a distorted understanding of Halal principles. Furthermore, the absence of specific digital ethics guidelines for Islamic-Halal content enables misuse of the “halal” label. This paper proposes an Islamic media ethics framework grounded in Maqasid Shariah and digital media literacy to promote authentic, responsible, and positive online discourse. The study underscores the need for proactive governance and collaboration between media actors, policymakers, and Halal authorities to safeguard the integrity of Islamic content in the digital sphere.